Reconstructing the War Injured Patient - Abu-Sittah, Ghassan Soleiman; Hoballah, Jamal J.; Bakhach, Joseph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive and state-of-the art approach to reconstruction of the war injured patient tailored to the types of injuries and patients mostly encountered from the Arab region over the past few years at the American University of Beirut Medical Center, one of the largest tertiary care and referral centers in the area and its affiliated hospitals. The book discusses in detail evidence of literature, new research data and new perspectives about the management and reconstruction of all types of injuries: ophthalmic, head and neck, upper and lower limb bone and soft tissue trauma, trunk, visceral and urogenital injuries as well as vascular and central and peripheral nerve injuries. It also highlights the social burden of these injuries as well as the importance of rehabilitation and psychological support for the war injured. The most recent findings of the change in the microbiology of these wounds and their treatment modifications are also discussed. Reconstructing the War Injured Patient will serve as a valuable resource for surgeons, clinicians and researchers dealing with and interested in the multiple facets of current war casualty care all the way from the battlefields to the long-term chronic rehabilitation. It includes concise yet comprehensive overviews of the current status of the war casualty patient reconstruction domain. It will help guide patient management based on evidence from literature, clinical and surgical experience and ongoing research. It will also help stimulate investigative efforts in this dynamic and active field of war medicine. .
Ballistics of Gunshot Wounds -- Biodynamics of Blast Injuries -- Management of Craniomaxillofacial Injuries -- The Management of Penetrating Neck Injuries -- Reconstruction of Periocular War Injuries -- Management of the Upper Limb Soft Tissue Injuries -- Management of Brachial Plexus Injuries -- Management of Upper Limb Fractures -- Lower Extremity Reconstruction -- Management of Peripheral Nerve Injuries -- Management of Lower Limb Fractures -- Abdominal Wall Reconstruction -- Contemporary Management of Urogenital Injuries -- Management of Central Nervous System War Injuries -- Vascular Trauma -- Early Microsurgical Management of Blast Injuries -- Amputations and Prostheses -- Healing the Scars Within: Psychological Support for the War-Injured -- Infections in Combat-Related Wounds.
Keywords: Medicine; Surgery; Plastic surgery; Vascular surgery; Urology; Medicine & Public Health; General Surgery; Plastic surgery; Vascular surgery; Urology